Variations of Malay Language in Sintang Raya - Patriantoro Patriantoro; Eka Fajar Rahmani (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
The research area in this study includes 1) a description of word variations, 2) differences in word variations between locations; (3) a language variation map, 4) language variation isogloss files. There are two methods used, namely descriptive and comparative methods. The descriptive method uses quantitative and qualitative techniques. The comparative method uses synchronous techniques. The comparative method is used to compare word variations in the research location. The calculation of the difference in word variations uses dialectometric formulas. The separation of language variations in the research location uses isogloss files. The results of the data analysis are 1) a description of the variations of the Malay language in 12 research locations; 2) the least difference in word variations in research locations 9-11 = 24 and the most difference in word variations in research locations 1-4 = 59; 3) based on the data analysis, the variations of words in the research locations resulted in different speech, sub-dialects, and dialects; 4) the linguistic distance in percentage is the least 24% in area 9-11 and the linguistic distance in percentage is the most 59% in research locations 1-4; 5) the map of word variations of the Malay language in Sintang Raya has 3 dialects; 6) the isogloss files show the existence of the most language variations as a separator of research has 3 dialects.